Anti-diabetic activity of Carica Papaya Linn in Alloxan-Induced diabetic rats. - Fazal, Jaweriya; Naz, Lubna; Sohail, Sumaira; Yasmeen, Ghazala; Iqbal Khan, Nazish; Zehra, Nazneen (International Journal of Endorsing Health Science Research, 2022)
Background: Type I Diabetes Mellitus (TIDM) is a disease known to occur in any age group, but most of the people affected are diagnosed in their mid-teenage. It is marked by hyperglycemia due to autoimmune destruction of insulin-producing pancreatic beta cells. Herbal treatment of DM has attracted attention in the last few decades because of its ability to improve diabetic complications such as nephrotic deterioration and oxidative stress. The present research is sought to determine the anti-diabetic potential of Carica Papaya leaf extract in Alloxan-induced diabetic rats. Methodology: For this study, eighteen healthy male Wistar rats weighing 150-200 g were made into three groups (n=6), two of which (Group II and Group III) were induced DM through Alloxan, whereas control (Group I) remained untreated. Group III diabetic rats were treated with 250 mg/kg body weight of papaya leaf extract after confirming hyperglycemia. Animals were sacrificed on the 22nd day for biochemical analysis. Results: This study showed that papaya leaf extract administration caused a significant reduction in the levels of plasma glucose, AST, ALP, ALT, serum urea, blood urea nitrogen (BUN), and creatinine in the papaya-treated group as compared to the Alloxan-treated group. It also increased plasma insulin levels compared to the diabetic-control (Alloxan-treated) group. Activity and concentration of major antioxidant enzymes such as CAT, SOD, and GSH in treated animals were also significantly increased compared to the diabetic (Alloxan-treated) group. Conclusion: Based on the findings, it is concluded that the C. Papaya leaf extract exhibits antidiabetic and antioxidative potential against alloxan-induced TIDM.